Secondary degradation of bio-oil degraded crumb rubber and preparation of stable degraded crumb rubber modified asphalt - Quanlei Wang; Yin Zhang; Mengzhen Zhao; Cong Li; Ashraf Aljarmouzi (Case Studies in Construction Materials, 2024)
Using bio-oil to desulfurize and degrade crumb rubber (CR) significantly enhances the compatibility between CR and asphalt, improving the workability of CR-modified asphalt and providing environmental and economic benefits. However, the secondary degradation of bio-oil degraded crumb rubber (ODR) in asphalt hinders the stability of ODR-modified asphalt. To optimize the mechanical performance of ODR-modified asphalt, the secondary degradation behaviors of ODR were investigated. The degree of CR degradation was determined by solubility testing, while the rheological properties and chemical structures of ODR-modified asphalt were characterized through rotational viscometer, dynamic shear rheometer, bending beam rheometer, and Fourier transform infrared spectrometer. The processes for preparing stable ODR modifier and ODR-modified asphalt were proposed to mitigate the damage caused by bio-oil and degraded CR to the high temperature mechanical properties of asphalt. The results show that at lower processing temperatures for ODR-modified asphalt, the volatilization of light components is predominant, while higher processing temperatures prompt secondary degradation of ODR. By stirring at 280°C for 2 hours to acquire moderately degraded CR, and then concentrating it at 220°C for 2 hours, a stable ODR less susceptible to secondary degradation can be obtained. The workability, temperature sensitivity, and low temperature cracking resistance of stable ODR-modified asphalt improve significantly. The reduction of ester group and increase in aromaticity restore the high temperature deformation resistance of ODR-modified asphalt. Further, the inclusion of composite SBS extends the range of rheological properties in ODR-modified asphalt, bolstering the application potential of ODR in asphalt pavement.